전기화학적 이산화탄소 환원을 통한 일산화탄소 생산 공정의 전과정평가 : 온실가스 저감 잠재량 분석 - 노고산(Kosan Roh) (Clean Technology, 28(1), 2022)
Electrochemical carbon dioxide (CO2) reduction technology, one of the promising solutions for climate change, can convert CO2, a representative greenhouse gas (GHG), into valuable base chemicals using electric energy. In particular, carbon monoxide (CO), among various candidate products, is attracting much attention from both academia and industry because of its high Faraday efficiency, promising economic feasibility, and relatively large market size. Although numerous previous studies have recently analyzed the GHG reduction potential of this technology, the assumptions made and inventory data used are neither consistent nor transparent. In this study, a comparative life cycle assessment was carried out to analyze the potential for reducing GHG emissions in the electrochemical CO production process in a more transparent way. By defining three different system boundaries, the global warming impact was compared with that of a fossil fuel-based CO production process. The results confirmed that the emission factor of electric energy supplied to CO2-electrolyzers should be much lower than that of the current national power generation sector in order to mitigate GHG emissions by replacing conventional CO production with electrochemical CO production. Also, it is important to disclose transparently inventory data of the conventional CO production process for a more reliable analysis of GHG reduction potential. 전기화학적 이산화탄소 환원 기술은 전기에너지를 이용하여 대표적인 온실가스인 이산화탄소를 유용한 기초 화학제품으로 전환시킬 수 있는 유망한 기술 중 하나다. 특히, 다양한 후보 제품 중 일산화탄소는 높은 Faraday 효율과 우수한 경제성을 나타내기 때문에 학계와 산업계의 많은 관심을 받고 있다. 과거 여러 연구진이 본 기술의 온실가스 저감 잠재량을 정량적으로 분석했으나, 분석 과정에서 도입된 과정과 사용된 인벤토리 데이터의 일관성 및 투명성에 문제가 제기된다. 본 연구에서는 전기화학적 이산화탄소 환원을 통한 일산화탄소 생산 공정의 온실가스 저감 잠재량 분석을 위한 전과정평가를 수행했다. 세 종류의 시스템 경계를 정의 후 각각의 지구온난화지수를 화석연료 기반 일산화탄소 생산 공정과 비교했다. 분석 결과, 전기화학적 일산화탄소 생산 기술을 도입하여 온실가스를 저감하기 위해서는 전해조 구동에 필요한 전기에너지의 배출계수가 현재 국내 발전부문의 배출계수보다 충분히 낮아야 한다는 점을 확인했다. 또한, 신뢰성 있는 온실가스 저감 잠재량 분석을 위해서는 기존의 화석연료 기반 일산화탄소 생산 공정의 인벤토리 정보를 투명하게 공개하는 것이 중요함을 밝혔다.